ANALSIS DAN PERANCANGAN KAMUS BAHASA ILMIAH TUMBUHAN BERBASIS ANDROID - Joni Alfian (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2021)
The scientific name of living things, especially plants, is one of the things that is basically very interesting to learn and know, because the scientific name of living things provides an important role, among others with scientific names it will easily know the characteristics, relationships of relatives, and interactions of living things in the environment. Knowledge of plant classification has generally been taught to high school students and MIPA students or biology majors, but interest in learning about plant taxonomy is still low due to the source of information that is not yet widely available. Therefore, the development of learning media is needed one of them by building an android-based plant scientific language dictionary application that can be one of the alternative learning media for students and students. The algorithm applied is sequential search that performs search faster because the search process is already in order. That way the interest in learning students and students about the scientific language of plants can be encouraged by the spirit in learning by using this learning medium. Based on the research that has been done, the application of the scientific language dictionary of plants can be used by students, students and the public as a means of learning in understanding the scientific names on each plant that is equipped with the alphabetic menu a-z and plant categories and search features to make it easier for users to find plant names